The correlation of acoustic and morphometric parameters of the optic nerve and anthropometric data in healthy young people - V. V. Neroev; T. N. Kiseleva; A. V. Baeva; E. K. Eliseeva; A. N. Zhuravleva; A. I. Ushakov; K. V. Lugovkina; T. V. Sudovskaya; I. V. Myshko (Российский офтальмологический журнал, 2022)
Purpose: to study the correlation between the acoustic and morphometric parameters of the optic nerve (ON) and anthropometric data in healthy young people.Material and methods. The research involved 24 healthy volunteers (48 eyes), including 9 men and 15 women, the average age was 25.0 ± 1.9 years. Anthropometry included measurements of height, weight, and body mass index (BMI). Ultrasound examination of the retrobulbar part of the ON included measurement of the thickness of the ON with and without sheath, echodensitometry of the ON, and ocular biometry. Using optical coherence tomography, we measured the intraocular part of the ON, including the registration of Bruch's membrane opening and ovality index.Results. The average ON thickness with the sheath was 4.6 ± 0.3 mm, and without sheath, 2.6 ± 0.2 mm. In men, ON with the sheath was thicker than in women (p = 0.001). The acoustic density of the parenchyma of the orbital part of ON was 101.2 ± 11.4 r.u. in women, the mean acoustic density of the ON was significantly higher than that in men. Correlation analysis revealed a statistically significant correlation between the height and the thickness of the ON with the sheath (r = 0.480). The strongest reliable correlation was established between the index of the ON thickness and body weight (r = 0.712) and BMI (r = 0.509) (p < 0.05). No statistically significant correlation was found between the morphometric parameters of the optic disc, anthropometry data and acoustic parameters of the ON.Conclusion. Studying the acoustic and morphometric characteristics of the intraocular and intraorbital parts of the ON in healthy young people, which included anthropometric data and gender characteristics, will contribute to the development more accurate diagnostic criteria of ON state evaluations.